Pharmacokinetics, Bioavailability, and Tissue Distribution Study of Angoroside C and Its Metabolite Ferulic Acid in Rat Using UPLC-MS/MS - Zhang, Chenning; Ma, Weidong; Zhang, Yonghong; Wang, Qibin; Qin, Caibin; Du, Shiming; Huang, Liangyong; Ye, Fang; Chen, Li; Zheng, Tao (Frontiers in Pharmacology, 2018)
Angoroside C is a phenylpropanoid glycoside compound isolated from the dried root of Scrophularia ningpoensis Hemsl., which possesses the effects of preventing ventricular remodelling, reducing pulmonary oedema, and reducing blood pressure, as well as having the properties of anti-platelet aggregation, hepatoprotection and anti-nephritis, etc. However, few investigations have been conducted on the absorption, distribution, metabolism, and excretion (ADME) study of angoroside C. Thus, a fast ultra-high performance liquid chromatography-tandem quadrupole mass spectrometry (UPLC-MS/MS) method was established for the determination of angoroside C and its metabolite ferulic acid in rat plasma and tissue homogenate; the two analytes were extracted from the biosamples using a simple protein precipitation with acetonitrile. The developed method was validated and successfully applied to the pharmacokinetics, bioavailability and tissue distribution study after the intragastric administration of angoroside C (100 mg/kg) or the intravenous administration of angoroside C (5 mg/kg), respectively. The results showed that angoroside C can be absorbed extremely quickly (Tmax=15 min), can be eliminated very rapidly (t1/2=1.26 h), and its oral bioavailability is only about 2.1%; furthermore, angoroside C was extensively distributed in all main organs (liver, heart, spleen, lung, kidney, and brain), and the highest concentration was detected in the lung 15 min after oral administration. This paper also indicated that angoroside C could be converted to the active metabolite ferulic acid in vivo; the maximum concentrations of ferulic acid in the kidney occurred at 6 h after oral administration. In summary, this study explored some of the pharmacokinetic characteristics of angoroside C in vivo, and the data produced could provide a basis for the further investigation of angoroside C.